Social accountability as a strategy to promote sexual and reproductive health entitlements for stigmatized issues and populations - Marta Schaaf; Grady Arnott; Kudzai Meda Chilufya; Renu Khanna; Ram Chandra Khanal; Tanvi Monga; Charles Otema; Christina Wegs (BMC, 2022)
Abstract Social accountability is often put forward as a strategy to promote health rights, but we lack a programmatic evidence base on if, when, and how social accountability strategies can be used to promote access to quality Sexual and Reproductive Health (SRH) care for stigmatized populations and/or stigmatized issues. In this Commentary, we discuss the potential advantages and disadvantages of social accountability strategies in promoting the availability of a full range of SRH services for excluded and historically oppressed populations. We accomplish this by describing four programs that sought to promote access to quality SRH care for stigmatized populations and/or stigmatized services. Program implementers faced similar challenges, including stigma and harmful gender norms among providers and communities, and lack of clear guidance, authority, and knowledge of Sexual and Reproductive Health and Rights (SRHR) entitlements at local level. To overcome these challenges, the programs employed several strategies, including linking their strategies to legal accountability, budgetary expenditures, or other institutionalized processes; taking steps to ensure inclusion, including through consultation with excluded or stigmatized groups throughout the program design and implementation process; specific outreach and support to integrating marginalized groups into program activities; and the creation of separate spaces to ensure confidentiality and safety. The program experiences described here suggest some general principles for ensuring that social accountability efforts are inclusive both in terms of populations and issues addressed. Further empirical research can test and further flesh out these principles, and deepen our understanding of context.